On a few Eastern Borderlands expressions in the Polish Language of Kiev Castellan Nikodem Kazimierz Woronicz - Sicińska, Katarzyna (Papers in Linguistics, 2025)
The article presents the features of the Borderlands speech occurring in the Polish language of Kiev Castellan Nikodem Kazimierz Woronicz († 1761), a representative of a noble family from the former South-Eastern Borderlands. Regional language facts are primarily grammatical. In the field of phonetics, five Borderlands features were confirmed, among others: disturbances in the realization of nasal vowels and the soft pronunciation of the consonants s, z, c in nouns ending in -yja, -ija. At the level of inflection, five Borderlands properties occurred, such as mixing masculine-personal and non-masculine- -personal forms of the verb in the 3rd person plural, and forms of the conditional with a doubled personal ending. At the syntactic level, three regional features were noted, e.g. numeral combinations of the type lat trzy and the syntax genetivus comparationis. The genesis of the recorded Borderlands elements varies; they are archaic features preserved in the peripheries of Borderlands and innovations resulting from internal linguistic evolution or Ukrainian interference. The discussed Southern Borderlands elements do not have numerous textual attestations, but their resources alone are significant.